The Vocational High School Teachers ‘Awareness Level and Implementation of the Students’ Learning Style Assessment - Mashoedah Mashoedah; Martin Hartmann; Herman Dwi Surjono; Zamroni Zamroni (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
As a reflection of teachers’ awareness of the students’ learning styles, teachers are required to have a good understanding of how the learning materials will be delivered to them through the teaching method and media, which are appropriate for their preferences. However, the uniqueness of learners’ learning styles has not become an important consideration for most of teachers. This study was aimed at finding out, to what extent vocational high school teachers were aware of the students’ learning styles. The data were collected through a survey and analyzed with the descriptive quantitative analysis. The results revealed that most of the respondents with the percentage of 65.7% (n=67) do not know the term of learning styles. Most of the respondents with the percentage of 77.6% do not assess the students’ learning styles. Although most of the respondents do not assess the students’ learning styles, the aspects of assessing the learning styles, using the instructional media appropriate with the students’ learning styles, and care about the students’ preferences in learning were categorized as good with the percentage of 43.3%, 71.6%, and 56.7% respectively. The overall of the vocational high school teachers’ awareness level of the students’ learning styles is categorized as good with the percentage of 76.1%.